Nitride Semiconductors. Issue 5 (May 2016) - Zhang, Guoyi; Shen, Bo; Zhang, Guoyi; Yu, Tongjun; Tang, Ning; Yang, Xuelin; Li, Shunfeng
Abstract: The 11th International Conference on Nitride Semiconductors (ICNS‐11) was held at Beijing International Convention Center during August 30 to September 4, 2015. The ICNS conference series is a premier platform for presenting research results in group III‐nitride semiconductors. The 11th one was the latest following the first conference held in Nagoya, Japan (TWN'95); the second in Tokushima, Japan (ICNS‐2); the third in Montpellier, France (ICNS‐3); the fourth in Denver, USA (ICNS‐4); the fifth in Nara, Japan (ICNS‐5); the sixth in Bremen, Germany (ICNS‐6); the seventh in Las Vegas, USA (ICNS‐7); the eighth in Jeju, Korea (ICNS‐8); the ninth in Glasgow, UK (ICNS‐9); and the tenth in Washington D.C. USA (ICNS‐10). The conference was very well attended with 821 attendees from 33 countries and areas, who had enjoyed a nice summer week in Beijing. A total of 733 abstracts were submitted to the conference, making 191 oral and 484 poster presentations. The Nitride Semiconductor field continues to grow and diversify, and as a result, the conference series ran four parallel sessions. The conference was divided into 44 different symposia, covering the entire spectra of III‐nitride semiconductor research and applications. Combining with 3 ramp sessions, all the contributors to this conference shared the general trends appearing in nitride semiconductor community, including the steady advancements in growth of GaN and AlN bulk crystals, greater attentions towards electronic devices, a movement from lateral to vertical devices, much progress in UV devices, more concern about point defects, and atomic level analysis on homogeneity or segregation of InGaN alloys. The organizers are particularly grateful to Nobel Prize laureates Hiroshi Amano and Shuji Nakamura for their great support to this conference. We are also very grateful to all members of the conference committees and invited speakers. We would especially like to acknowledge the sponsors and agencies for their financial support. Thanks also to the 38 exhibitors who participated in the meeting. Finally, we especially want to express our great appreciation to Overseas Exchange Center of Peking University and Beijing International Conference Center. Altogether 109 submissions were received for the conference proceedings to be published in the journal of physica status solidi, based on their standard evaluation procedures. Among them, 76 articles have been accepted for publication in this special volume, with 28 being accepted for special sections in Phys. Status Solidi A and Phys. Status Solidi B. We are grateful to the editorial support provided by Stefan Hildebrandt, Julia Hübner, Irina Juschak and their team in bringing the proceedings together. Finally, we thank all those who attended and contributed to making ICNS‐11 such an enjoyable and successful conference and look forward to meeting you all again in Strasbourg at ICNS‐12 in 2017.